ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE DALAM PUISI “KI HAJAR DEWANTAR “ KARYA SANUSI PANE - Sihombing, Rika Chintia; Hanna Geovanni Tampubolon; Mei Pitriani Manurung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
To explore the semiotics of Charles Sanders Peirce found in Sanusi Pane’s poetry Ki Hajar Dewantara, the researcher utilizes a hermeneutic approach and qualitative method. In particular, this study looks at the meanings of symbols, icons, and indices as part of Peirce's trichotomy of signs, where indices are based on cause-and-effect relationships (like